The effects of prenatal exposure to temperature extremes on birth outcomes - Chen, Xi; Tan, Chih Ming; Zhang, Xiaobo; Zhang, Xin (Institute of Labor Economics, 2020)
This paper investigates the effects of prenatal exposure to extreme temperatures on birth outcomes – specifically, the log of birth weight and an indicator for low birth weight – using a nationally representative dataset in rural China. During the span of our data (i.e., 1991–2000), indoor air-conditioning was not widely available and migration was limited, allowing us to address identification issues endemic in the climate change literature related to adaptation and location sorting. We find substantial heterogeneity in the effects of extreme temperature exposure on birth outcomes. In particular, prenatal exposure to heat waves has stronger negative effects than exposure to cold spells on survivors.